1997
DOI: 10.1038/ki.1997.505
|View full text |Cite
|
Sign up to set email alerts
|

Serum oxalate microassay using chemiluminescence detection

Abstract: Determination of serum oxalate concentration is important for the diagnosis and monitoring of hyperoxalurias, and extends to patients with all types of renal disease. Approximately 5 to 10 ml of blood is required for each test by conventional methods, and the test is not adapted for use in children. We developed a highly sensitive method that limits the volume of blood required for the test. This new and sensitive tool to detect H2O2 can be successfully substituted for the conventional, and expensive, colorime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The determination of plasma oxalate based on different methodological approaches in adult populations also provided similar outcomes [21,27,32,34,36,37,39,41,44,64]. Several methods were used to evaluate normative data on plasma oxalate in pediatric populations; however, numbers of subjects included and age representation were limited or confined to one gender [43,[45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The determination of plasma oxalate based on different methodological approaches in adult populations also provided similar outcomes [21,27,32,34,36,37,39,41,44,64]. Several methods were used to evaluate normative data on plasma oxalate in pediatric populations; however, numbers of subjects included and age representation were limited or confined to one gender [43,[45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Barratt et al [45] carried out a study of 33 children using the enzymatic method and showed plasma oxalate levels ranging between 0.78-3.02 µmol/L. Gaulier et al [46] used a chemiluminescence technique to determine plasma oxalate levels in 30 healthy children: the mean value was 3.3± 1.7 µmol/L, whereas slightly higher levels were reported by Hoppe et al in a cohort of 23 boys (6.2±1.06 µmol/L) and 27 girls (6.63±1.09 µmol/L) [47]. The enzymatic method used in our study is regarded as a simple, cost effective, and accurate tool for assessing plasma oxalate concentration [43,53,57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent report, the oxalic acid concentration is elevated in the serum of dialysis patients (48.5 and 17.7 lmol L À1 before and after dialysis, respectively) [51]. The concentration of oxalate in blood from a healthy person is about 2 lmol L À1 [52]. Furthermore, during metabolic acidosis, the concentration of bicarbonate in the serum decreases, so the relative concentration of oxalate may be enhanced.…”
Section: Comparison Of Metal-binding Affinity To Native-and Asialo-htfmentioning
confidence: 95%
“…The clinical consequences of this overproduction are due to three properties of oxalate: it is an end product of metabolism, it has a strong affinity for calcium, and the resulting salts have a very low solubility [2]. Fortunately, the body clearance of oxalate, which is quite solely accomplished by the kidney, is very efficient and, normally, plasma levels of oxalate are in the order of mol/l, with a daily production and excretion of 20 -50 mol [3][4][5].The main characteristics of oxalate turnover in man are depicted in table 1. At the physiological pH oxalic acid is virtually all dissociated and strongly binds to calcium.…”
mentioning
confidence: 99%